2020
DOI: 10.1021/acs.est.9b07658
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Crude Oil Induces Retinal Apoptosis and Impairs Visual Function in Fish

Abstract: Polycyclic aromatic hydrocarbons (PAHs) present in crude oil are known to impair visual development in fish. However, the underlying mechanism of PAH-induced toxicity to the visual system of fish is not understood. Embryonic zebrafish (Danio rerio) at 4 h post fertilization were exposed to weathered crude oil and assessed for visual function using an optokinetic response, with subsequent samples taken for immunohistochemistry and gene expression analysis. Cardiotoxicity was also assessed by measuring the heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 52 publications
5
27
0
1
Order By: Relevance
“…In PFOA-exposed F0 larvae, rpe65a and atp6v0e1 were downregulated. Downregulation of rpe65a is associated with retinal degeneration in zebrafish [47], and loss of RPE65 function leads to blindness in humans [48]. Atp6v0e1 is involved in visual-motor behavior [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PFOA-exposed F0 larvae, rpe65a and atp6v0e1 were downregulated. Downregulation of rpe65a is associated with retinal degeneration in zebrafish [47], and loss of RPE65 function leads to blindness in humans [48]. Atp6v0e1 is involved in visual-motor behavior [49].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, human health research and policies are mainly concerned with the directly exposed subject. In the F0 generation, PFOA exposure was associated with hypoactivity, with a potential visual-motor impact occurring via the downregulation of vision-related genes rpe65a and atp6v0e1 [47,49]. Similarly, PFOS-exposed larvae were also hypoactive in the light and had a downregulated photoreceptor gene (kif3c) [61].…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons in crude oil have been reported to impair vision in fish. Magnuson et al ( 2020 ) found out that embryonic zebrafish ( Danio rerio ) exposed to crude oil exhibited cell death in the retina and bradycardia. A reduction in cardiovascular performance was observed in the Gulf killfish ( Fundulus grandis ) exposed to oil.…”
Section: Environmental Pollution As a Results Of Crude Oil Exploration And Processingmentioning
confidence: 99%
“…Disruption of these pathways affected retinal histology as well as visual acuity (as determined by optomotor response) in a PAH dose-dependent manner in mahi-mahi (Xu et al 2018), red drum, and sheepshead minnows (Magnuson et al 2018). A subsequent study using slick oil and zebrafish determined that disruption of these gene expression pathways and visual acuity were consistent with a dose-dependent loss of glial cells supporting the neuronal network in the retina (Magnuson et al 2020). These data suggest that exposure to oil may disrupt eye development and function across a number of fish species.…”
Section: Fishmentioning
confidence: 91%